Peningkatan Keterampilan Menulis Kreatif Puisi Melalui Metode Discovery Inquiry Siswa Kelas VII SMP N 2 Marioriwawo (International Forum of Researchers and Lecturers, 2023)
This study aims to improve students' ability to write poetry creatively through the discovery-inquiry method for class VII students of SMPN 2 Marioriwawo. This research is a class action research (PTK) meaning class-based research in which the procedure is carried out with various actions (action research). Classroom action research can be defined as a part in the form of a reflective study by action actors, which is carried out to increase the rational ability of the actions taken and improve the conditions in which the learning practices are carried out. This classroom action research is intended to develop new skills or approaches to solving problems with direct application in schools. Classroom action research is also carried out thematically by following certain procedures or steps. This study uses a class action research design (CAR) with two cycles, namely the action process in cycle I and cycle II. In the first cycle aims to determine students' skills in creative writing poetry. While the results of the process research held in cycle II aimed to determine the level of students' abilities in writing poetry after making improvements in student teaching and learning activities. Cycle I aims to determine students' poetry creative writing skills, from cycle I it is used as a reflection to carry out cycle II. While the second cycle aims to find out the increase in students' poetry creative writing skills through the Discovery-Inquiry method after making improvements to the implementation of the teaching and learning process based on cycle I. Students' poetry creative writing test scores in cycle I reached an average of 56% of students in class or the class doesn't understand about creative poetry writing. The average results of cycle II tests reached an average of 75% for the number of students in the class or in the good category. The students' poetry test results from Cycle I to Cycle II increased by 19%. This increase was caused by the adaptability of students in cycle II with the discovery-inquiry learning method used by researchers.